Complications of tube thoracostomy in trauma. Issue 2 (1st March 2000) - Bailey, R C
Abstract : Objective —To assess the complication rate of tube thoracostomy in trauma. To consider whether this rate is high enough to support a selective reduction in the indications for tube thoracostomy in trauma. Methods —A retrospective case series of all trauma patients who underwent tube thoracostomy during a 12 month period at a large UK teaching hospital with an accident and emergency (A&E) department seeing in excess of 125 000 new patients/year. These patients were identified using the hospital audit department computerised retrieval system supplemented by a hand search of both the data collected for the Major Trauma Outcome Study and the A&E admission unit log book. The notes were assessed with regard to the incidence of complications, which were divided into insertional, infective, and positional. Results —Fifty seven chest drains were placed in 47 patients over the 12 month period. Seven patients who died within 48 hours of drain insertion were excluded. The commonest indications for tube thoracostomy were pneumothorax (54%) and haemothorax (20%); 90% of tubes were placed as a result of blunt trauma. The overall complication rate of the procedure was 30%. There were no insertional complications and only one (2%) major complication, which was empyema thoracis. Conclusion —This study reveals no persuasive evidence to support a selective reduction in the indications for tube thoracostomy in trauma. A larger study to confirm or refute these findings must be performed before any change in established safe practice.